Orthodontic-logaoedic treatment using a modified Hawley device. - Clotilde Mora Pérez; Raúl López Fernández; Liliam Farray Domínguez; Raiza I. Domínguez Garcia; Yordanis Boza Mejias; Danibis Boza Mejias (Medisur)
Introduction: According to the World Health Organization, malocclusion ia a higly risky entity that is placed in the 3rd position worldwide within oral diseases. There is a great relation among dento-maxillofacial disorders, dental vestibulo version, open bite and speaking disorders. Occlusion disorders can be more or less severe and can involve almost all the structures of the oral cavity. Objective: To check the usefulness of the modified Hawley´s device in patients with dental malocclusion produced by deforming habits and carriers of dyslalia. Method: Observational, analytico-comparative study carried out at the elementary school ¨Guerrillero Heroico¨ from Cienfuegos Municipality . A non-probabilistic sample of 32 patients was taken for this study; patients to whom 2 measurements were made. The variables under study were: Number of the Clinical record, Files, Dentomaxilofacial anomalies, sucking of the thomb, atypical deglussion, analysis of the pronunciation and levels of articulation. Hawley´s device was placed with an oval perforation at the level of the palatal folds changing the traditional form of the device. Result: There is a prevalence of malocclusion Class I. The most common maxillofacial disorders are: vestibulo version (87,5%), increased enhancement (84,4 %) and abnormal bilabial closure (68,8 %). Dyslalias were reduced during treatment from 81,2 % to 28,1 % at the end of treatment.